The challenges of police-community collaboration: identity manoeuvres and power struggles in a neighbourhood based meeting. Issue 9 (2nd September 2018) - Mangan, Anita; Thomas, Robyn; Davies, Annette; Gasper, Roz
ABSTRACT: The turn to collaborative governance is a key feature of the New Public Governance environment in many Western economies. Within the UK, successive governments have mandated policing organizations to engage in public service partnerships and collaborate with communities. This paper examines one such collaborative arrangement, namely, neighbourhood public meetings. Drawing on a theoretical framing of the dynamic relationship between identities, agency and power, we critically explore how individuals seek to persuade, defend and legitimate their values, beliefs and practices in collaborative situations. The paper provides a nuanced exploration of the challenges of collaboration for both public servants and community members.